2005
DOI: 10.1161/01.res.0000164321.91452.00
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulator FTY720 Induces eNOS-Dependent Arterial Vasodilatation via the Lysophospholipid Receptor S1P 3

Abstract: Abstract-The novel immunomodulator FTY720 is effective in experimental models of transplantation and autoimmunity, and is currently undergoing Phase III clinical trials for prevention of kidney graft rejection. FTY720 is a structural analogue of sphingosine-1-phosphate (S1P) and activates several of the S1P receptors. We show that FTY720 induces endothelium-dependent arterial vasodilation in phenylephrine precontracted mouse aortae. Vasodilation did not occur in thoracic aortic rings from eNOS-deficient mice, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
78
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(85 citation statements)
references
References 48 publications
5
78
1
1
Order By: Relevance
“…With the use of S1P 3 knockout mice, for example, it was recently shown that HDLs, known to carry S1P, and the immunomodulator and S1P receptor agonist FTY720 induce an endothelium-and NO-dependent vasorelaxation via the S1P 3 receptor in vitro and ex vivo. 34,42 Taken together, these data suggest that activation of the endothelial AT 1 receptor by Ang II leads to a modulation of the sphingolipid metabolism, resulting in increased NO production. This is most likely the result of increased sphingosine kinase activity leading to increased production of S1P that subsequently stimulates (an) endothelial S1P receptor(s).…”
Section: Expression Of S1p Receptor and Sphingosine Kinase Subtypes Imentioning
confidence: 77%
“…With the use of S1P 3 knockout mice, for example, it was recently shown that HDLs, known to carry S1P, and the immunomodulator and S1P receptor agonist FTY720 induce an endothelium-and NO-dependent vasorelaxation via the S1P 3 receptor in vitro and ex vivo. 34,42 Taken together, these data suggest that activation of the endothelial AT 1 receptor by Ang II leads to a modulation of the sphingolipid metabolism, resulting in increased NO production. This is most likely the result of increased sphingosine kinase activity leading to increased production of S1P that subsequently stimulates (an) endothelial S1P receptor(s).…”
Section: Expression Of S1p Receptor and Sphingosine Kinase Subtypes Imentioning
confidence: 77%
“…74 A recent study reported that FTY-720 mediates eNOS-dependent vasorelaxation in phenylephrinepreconstricted mouse thoracic aorta preparations by way of S1P 3 receptor activation. 75 Collectively these studies help establish that treatment with S1P leads to physiologically relevant amounts of NO production in intact blood vessels.…”
Section: Vasoconstriction Pathways Elicited By Sphingosine-1-phosphatmentioning
confidence: 88%
“…45 An S1P 1 -selective agonist may act directly on macrophage proliferation and trafficking. [26][27][28][29]46 An in vivo proliferation assay demonstrated that CYM did not affect macrophage proliferation. Increasing amounts of data have indicated that the lower number of macrophages in the inflamed tissues of FTY720-treated mice could be an indirect effect of vascular permeability and monocyte recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…CYM (3 mg/kg), 5,27,28 control water, or FTY720 was intraperitoneally injected daily from day 21 to day 3 post allogeneic bone marrow transplantation (BMT). Ten mice per group were monitored daily for survival, were weighed every 3 days, and were thereafter examined for the clinical characteristics of aGVHD.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation